Antibacterial Action: Antibacterial Action of Nanoparticles by Lethal Stretching of Bacterial Cell Membranes (Adv. Mater. 52/2020). Issue 52 (28th December 2020) - Linklater, Denver P.; Baulin, Vladimir A.; Le Guével, Xavier; Fleury, Jean‐Baptiste; Hanssen, Eric; Nguyen, The Hong Phong; Juodkazis, Saulius; Bryant, Gary; Crawford, Russell J.; Stoodley, Paul; Ivanova, Elena P.
Abstract : The antibacterial action of large (>10 nm) spherical gold nanoparticles is demonstrated by Elena P. Ivanova and co‐workers in article number 2005679 to be attributed to the combined stretching and rupture of the bacterial cell membrane. The newly discovered mechanical modes of antibacterial action pose varied implications for the use and application of nanomaterials. The mechanical killing of bacteria in liquids by surface‐active nanom aterials provides another platform from which to combat the global health crisis of antibiotic resistance.